2019
DOI: 10.1016/j.cgh.2019.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Helicobacter pylori Exposure and Decreased Odds of Eosinophilic Esophagitis—A Systematic Review and Meta-analysis

Abstract: Background & Aims: Previous or current infection with Helicobacter pylori (exposure) has been reported to protect against eosinophilic esophagitis (EoE), perhaps due to H pylori -induced immunomodulation. However, findings vary. We performed a systematic review and meta-analysis of comparative studies to more clearly define the association between H pylori exposure and EoE. Methods: We sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 61 publications
(77 reference statements)
0
46
0
4
Order By: Relevance
“…As additional support, we demonstrated that individuals exposed to H pylori but who were CagA seronegative had similar odds of IBD, CD and UC as individuals without H pylori exposure. We further compiled a complementary synthesis of relevant experimental data, which provide a platform of support for biological plausibility of CagA as one critical mediator of the protective association observed clinically between H pylori exposure and odds of IBD, as well as very likely other immune‐mediated diseases …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As additional support, we demonstrated that individuals exposed to H pylori but who were CagA seronegative had similar odds of IBD, CD and UC as individuals without H pylori exposure. We further compiled a complementary synthesis of relevant experimental data, which provide a platform of support for biological plausibility of CagA as one critical mediator of the protective association observed clinically between H pylori exposure and odds of IBD, as well as very likely other immune‐mediated diseases …”
Section: Discussionmentioning
confidence: 99%
“…When present, host responses to H pylori strains expressing CagA are more robust in children, which is when H pylori exposure most often occurs . Indeed, these early H pylori associated immunomodulatory effects might also protect against immune‐mediated diseases other than IBD, such as asthma and allergy . One cross‐sectional analysis of 7663 adults from the Third National Health and Nutrition Examination Survey found that the inverse association between H pylori and asthma, allergic rhinitis and allergies was more pronounced amongst younger individuals and amongst those who were CagA seropositive …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review with meta-analysis, including 11 studies and 377 795 patients, H pylori was found to be associated with a decreased risk of eosinophilic oesophagitis (OR 0.63; 95% CI, 0.51-0.78). 95 The relationship between allergy and H pylori was also investigated in preclinical models. Perinatal exposure to H pylori extract or to VacA was found to protect mice against allergic airway inflammation.…”
Section: Allergic Disordersmentioning
confidence: 99%
“…A decline in H pylori prevalence over the past decades corresponds temporally and geographically to an increased incidence of eosinophilic esophagitis (EoE) and other immune‐mediated diseases. A meta‐analysis by Shah et al included 11 observational studies incorporating over 350 000 individuals and found that H pylori infection is associated with a 37% reduced risk of EoE . Nine of these studies defined EoE as 15 or more eosinophils per high‐power field (eos/hpf) together with esophageal symptoms.…”
Section: Esophageal Diseasesmentioning
confidence: 99%